2021
DOI: 10.1007/s10964-021-01433-z
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Dual Systems Theories of Adolescent Delinquency in a Normative Longitudinal Cohort Study of Youth

Abstract: Dual systems theories of adolescent risk-taking propose that the socioemotional and self-regulation systems develop at different rates, resulting in a peak in sensation-seeking in adolescence at a time when self-regulation abilities are not yet fully mature. This “developmental imbalance” between bottom-up drives for reward and top-down control is proposed to create a period of vulnerability for high-risk behaviors such as delinquency, substance use, unprotected sex, and reckless driving. In this study, data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Likewise, our results may reflect a tendency for adolescents to rebel against parental control and expectations; and this may require as much self-regulation, on average, as conforming to the expectations. Another explanation could be that self-regulation skills do not fully mature until after adolescence (and in adolescence they may be temporarily undermined by a peak in reward drive) (Murray et al, 2021), so perhaps these mechanisms may become more relevant to personality change in the transition from adolescence to emerging adulthood.…”
Section: The Role Of Self-regulation Effortsmentioning
confidence: 99%
“…Likewise, our results may reflect a tendency for adolescents to rebel against parental control and expectations; and this may require as much self-regulation, on average, as conforming to the expectations. Another explanation could be that self-regulation skills do not fully mature until after adolescence (and in adolescence they may be temporarily undermined by a peak in reward drive) (Murray et al, 2021), so perhaps these mechanisms may become more relevant to personality change in the transition from adolescence to emerging adulthood.…”
Section: The Role Of Self-regulation Effortsmentioning
confidence: 99%
“…These methods help to organize individual differences in developmental trajectories into a small number of more manageable and potentially clinically useful developmental classes. Sex/gender differences can then be examined via multi‐group models (Diamantopoulou et al., 2011 ), sex/gender‐stratified analyses (Murray, Zhu, et al., 2021 ), or by predicting developmental trajectory class membership from sex/gender (Murray et al., 2020 ; Ohannessian et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…While this presents some issues, considering that this population does indeed present higher risk for engagement in risky behaviors, this population may be particularly relevant for examining these processes. Being that impulse control and sensation-seeking are risk factors for offending (Armstrong et al, 2020;Murray et al, 2021), it would generally be expected that these constructs would be observed at more problematic levels among JIY than same-age peers in the general population. While direct comparison with the specific measures used in the present study is not possible, this does indicate some additional concern regarding generalizability of findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several control variables were also included in analyses in order to mitigate bias in estimation of effects. The first of these was gender at baseline, as past research has indicated gender differences in dual systems constructs (Murray et al, 2021). Gender was coded as a binary variable that delineated male and female participants (0 = Male; 1 = Female).…”
Section: Methodsmentioning
confidence: 99%